A nanohybrid synthesized by polymeric assembling Au(I)-peptide precursor for anti-wrinkle function - Liu, Dan; Huang, Yinong; Mao, Jian; Jiang, Cheng; Zheng, Lei; Wu, Qimei; Cai, Hong; Liu, Xiaojing; Dai, Jingyao (Frontiers in Bioengineering and Biotechnology, 2022)
A major sign of aging is wrinkles (dynamic lines and static lines) on the surface of the skin. In spite of Botulinum toxin's favorable therapeutic effect today, there have been several reports of its toxicity and side effects. Therefore, the development of an effective and safe wrinkle-fighting compound is imperative. An antioxidant-wrinkle effect was demonstrated by the peptide that we developed and synthesized, termed Skin Peptide. Aiming at the intrinsic defects of the peptide such as hydrolysis and poor membrane penetration, we developed a general approach to transform the Skin Peptide targeting intracellular protein-protein interaction into a bioavailable peptide-gold spherical nano-hybrid, Skin Pcluster. As expected, the results of in vitro experiments revealed that Skin Pcluster can reduce the content of the neurotransmitter acetylcholine, and then inhibit neuromuscular signal transmission. Additionally, human experiments demonstrated a significant de-wrinkle effect. Moreover, Skin Pcluster is characterized by a reliable safety profile. Consequently, anti-wrinkle peptides and Skin Pcluster nanohybrids demonstrated innovative anti-wrinkle treatments and have significant potential applications.